Modelling, controlling and regulating the energy consumption of a hybrid vehicle - Tarraf Mohammad; V. V. Gayevskiy; Deeb Muhammad (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The increasing scarcity and cost of fossil fuels, combined with the awareness of global warming issues, have led in recent years to the development of hybrid vehicles, which are now an industrial solution to reduce fuel consumption and thus CO2 emissions and pollutants. Against this background, a number of research programmes have recently been conducted on hybrid vehicle modelling to determine the optimal architecture, simulate energy behaviour and define energy management laws; hybrid vehicle design to validate components and theoretically defined energy management laws; and vehicle testing to verify vehicle performance under real-world conditions. This paper focuses on modelling and simulation of a hybrid vehicle with two energy sources: an internal combustion engine and an electric motor. A ‘series-parallel’ hybrid scheme is adopted for modelling, so each component is modelled separately. The vehicle model taken for modelling consists of a set of different component blocks by connecting them in a structured manner. A control strategy is developed to control the powertrain, the role of which is to select at each instant of time the optimal power allocation between the different power sources in such a way as to minimize fuel consumption and emissions.